DIGITAL NARRATIVES ON SOCIAL MEDIA AS AN INSTRUMENT FOR LOCAL CULTURAL PRESERVATION: A DIGITAL CULTURAL COMMUNICATION APPROACH - Pupi Indriati Zaelani; Alin Yulianti; Ahmad Muzakki (PT Altin Riset Publishing, 2026)
This study examines the role of digital narrative as an instrument for preserving local culture in the midst of the challenges of globalization and digitalization. The focus of the study is the Instagram account @pesona.indonesia, which is managed by the Ministry of Tourism and Creative Economy of the Republic of Indonesia, as a medium for tourism and cultural promotion. Through a qualitative approach with a content analysis method, this study describes the form of digital narrative, analyzes the integration of local cultural values, and assesses the contribution of audience interaction in cultural preservation. The results of the study show that the digital narrative on the @pesona.indonesia account is built through a combination of cinematic visual storytelling and the use of distinctive, persuasive, and informative language. Content such as Gelar Melayu Serangpun, Kamist Toraja, and the Sabang–Merauke narrative are evidence of how visual elements, texts, and cultural symbols combine to form captivating representations and create emotional attachment. The integration of local cultural values, such as collectivity, togetherness, and identity, is carried out authentically and contextually through the visualization of traditions, arts, culinary, and customs, complete with explanations of their meanings and philosophies. Furthermore, audiences play an active role in preserving culture through high levels of engagement (likes, comments, shares), the formation of user-generated content (UGC), and the potential for collaboration. These interactions not only expand the reach of cultural messages but also create spaces for dialogue and collective participation. Theoretically, this study enriches the study of digital cultural communication, while practically, providing strategic recommendations for social media managers and communication practitioners in designing engaging digital content while strengthening national cultural identity.